Modelagem da germinação e do alongamento de plântula de espécies de plantas daninhas poáceas - Hoffmann, Andrea Ferreira (2017)
Weeds are harmful to crops and seedling emergence prediction models represent a potentially powerful tool for weed management. Considering that seedling emergence comprises the processes of seed germination and radicle and shoot elongation, both processes need to be modelling to create models for predicting seedlingsemergence. Consequently, we aimed to model the seed germination and seedling radicle and shootelongation of the grass weed species Eleusine indica (L.) Gaertn., Digitaria insularis(L.) Fedde. e Digitaria horizontalis Willd., to provide information on seedlings emergence biology of thesethree species to help incorporate emergence prediction models into weed management in crops. The research held two chapter, in which we attempted: (1) to analyse the water and temperaturerelation on seed germination by verifying whether these factors act separately or combined onseed germination, and how this effect affects the germination biology of different species of weeds; (2) to evaluate the temperature effect on radicle-shoot elongation process of E. indica, D. insularise D. horizontalis. In the first chapter, the seed germination rate was modelled by combiningnine temperature regimes and eight water potentials with the variant of the Cox proportional model with discrete time. Regarding the temperature range for seed germination: E. indicadisplayed a variation of 40 ºC (from 12,5 to 42,5 ºC), D. insularisof 10 ºC (from 27,5 to 37,5 ºC), and D. horizontalisof 35 ºC (from 17,5 to 42,5 ºC). The seed germination rate showed different temperature responses to different water potentials for the three species studied. We found that the germination behaviour varies with the species and with the combination of water potentialand temperature. The Cox model application provided a new approach to analyse the water and temperature relation on weed seed germination. In the second chapter, the radicle-shoot elongationwas modelled with nine temperature regimes by fitting a three-parameter logistic model. Radicle and shoot elongation processes occurred in the temperature range from 12,5 to 42,5 ºC for all three species evaluated. However, the temperature specifically affected the radicle and shoot elongation process of the species, presenting different effects on elongation velocity and extension in each process and species studied. We showed to be possible to derive weed management strategies by analysing the general behaviour of seed germination and seedling elongation of the species studied. Actually, the information produced by modelling these processes are not readily applicable, first it seems mandatory to understand the process as a whole, and then to transform them into applied knowledge and tools to strengthen the weeds management of difficult control species, such as D. insularis and E. indica, preventing that easy control species like D. horizontalis become a problem.